Significance Of Cervical Cytology Screening (Pap Smear) In The Detection Of Precancerous Cervical Lesions - Al-Shammari, Issraa A.; Al-Alwan, Nada A. (Journal of the Faculty of Medicine Baghdad, 2007)
Summary: Background: The incidence of cancer of the cervix is comparatively low in Iraq, as in most other Islamic countries. Pre invasive lesions of the uterine cervix can be detected by Pap smears in their preclinical course, a fact which documents the significant role of cervical cytology in gynecological practice.Objective: To emphasize the role of cervical cytopathology (Pap smears) in the detection and follow up of various cervical lesions that may predispose to cervical carcinoma with special emphasis on Cervical Intraepithelial Neoplastic (CIN) conditions or dysplasias.Patients and Methods: This retrospective study M’as performed on 1500 women aged 20 years and above who attended the private clinical laboratory of the senior investigator during the period betM'een (May 2000 to May 2001). Cases were randomly selected. All relevant clinico-pathological data were recorded within a standardized interview report. After careful examination of the external genitalia, a Pap smear M’as obtained using Ayre's wooden spatula. Results were recorded and statistically analyzed.Results: Cytological diagnosis revealed:1065 cases (71.01%) of non specific cervicitis.392 cases (26.13%) of specific cervicitis.30 cases (2%) of cervical polyp.172 cases (11.47%) of CIN! (mild dysplasia).31 cases (2.07%) of CINj (moderate dysplasia).10 cases (0.67%) ofCIN} (severe dysplasia).According to the Bethesda system, atypical squamous cells of undetermined significance (ASCUS) M’as the most common epithelial cell abnormality representing (24.27%) of total group studied, while low grade squamous intraepithelial lesions (LGSIL) and atypical glandular cell of undetermined significance (AGUS) represented (13.27 %) and ( 16.2 %) of total group studied respectively. High grade squamous intraepithelial lesions (HSIL) were detected in (2.73 %) of the examined smears. Clinical examination revealed that the grades of CIN were higher in patients with older age groups and a statistically significant correlation M’as shown between parity and the severity of cervical lesions. Cervical erosions, hypertrophy and congestion were reported in a significant proportion of cases among our sudy population.Conclusion: Pap smear cytology remains as one of the most effective tools used in the early detection and follow up of many gynecological disorders specifically precancerous lesions of the uterine cervix.. Cytological diagnosis of these lesions with treatment of the associated inflammations could be helpfid in preventing their progression into more serious cervical pathology.